Patient and Health-care Professional Satisfaction with a New, Simple, High Accuracy Blood Glucose Meter with Color Range Indicator - Katz, Laurence B. (Indian J Endocrinol Metab, 2017)
BACKGROUND: Accurate self-monitoring of blood glucose (BG) is a key component of effective self-management of glycemic control. METHODS: The OneTouch Select Plus Simple™ (OTSPS) BG monitoring system (BGMS) was evaluated for accuracy in a clinical setting. RESULTS: OTSPS was accurate over a wide glucose range and met lay user and system accuracy BG standards described in ISO 15197:2013. Patients also used OTSPS for a 1-week trial period and reported their level of satisfaction with meter features. In a separate study, health-care professionals (HCPs) in India naïve to OTSPS experienced OTSPS online using a variety of interactive demonstrations of the BGMS and answered questions about its potential utility to their patients. SUMMARY: Patients and HCPs felt the features of OTSPS, including a color range indicator, could provide significant benefits to them and their patients.